2022
DOI: 10.1108/jeee-03-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Is entrepreneurship enough to achieve superior performance in SMEs in emerging countries? Multiple mediation of market orientation and marketing capabilities

Abstract: Purpose The purpose of this paper is to analyze the multiple mediation role of both market orientation (MO) and marketing capabilities (MC) in the relationship between entrepreneurial orientation (EO) and performance (OP), given that the results of previous studies are not conclusive. Consequently, this relationship can be more complex than a direct relationship. Design/methodology/approach Using structural equation models, the proposed conceptual model is tested with data from 154 small and medium-sized ent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 109 publications
0
1
0
Order By: Relevance
“…This finding is consistent with the study conducted by Kamboj & Rahman (2017), which states that market orientation has a positive impact on market capabilities. The study conducted by Rincon et al (2021) also found similar results that market orientation, besides creating strategies focused on understanding market needs, also shapes the company's strategic response to market demands and opportunities. That is why market orientation enhances the development of marketing capabilities, where companies generate strategies (product, price, advertising, and distribution) to effectively respond to market demands.…”
Section: Market Orientation and Marketing Capabilitiesmentioning
confidence: 53%
“…This finding is consistent with the study conducted by Kamboj & Rahman (2017), which states that market orientation has a positive impact on market capabilities. The study conducted by Rincon et al (2021) also found similar results that market orientation, besides creating strategies focused on understanding market needs, also shapes the company's strategic response to market demands and opportunities. That is why market orientation enhances the development of marketing capabilities, where companies generate strategies (product, price, advertising, and distribution) to effectively respond to market demands.…”
Section: Market Orientation and Marketing Capabilitiesmentioning
confidence: 53%
“…After disentangling a spectrum of extant literature regarding entrepreneurship growth through a VC funding model, we discover that a growing body of evidence offers mixed conclusions (Figure 3). As seen in Figure 3, 44% of the reviewed articles largely focused exclusively on entrepreneurship and SME development (e.g., Abubaker, 2015; Kloepfer & Castrogiovanni, 2018;Möller & McCaffrey, 2021;Cruz Rincon et al, 2022;Endris & Kassegn, 2022) , this was followed by 21% of articles published exclusively about venture capital (e.g., Keuschnigg and Soren, 2004;Messica & Agmon, 2008;Iriyama et al, 2010;Groh & Liechtenstein, 2011;Portmann & Mlambo, 2013) while 18% studied VC and firm-level performance (Ajagbe & Ismail, 2014;Lechner et al, 2016;Kato & Germinah, 2022;Sriyono et al, 2021;Dai et al, 2022;(Kato & Germinah, 2022). Many of these studies are often narrowed to firm-level performance of entrepreneurship efforts, declining to describe the interaction between entrepreneurship and VC investment efforts Bruton et al, (2008).…”
Section: A Venture Capital and Entrepreneurship Development Empirical...mentioning
confidence: 99%
“…Recently, social media and social networks have gained prominence as primary platforms for shaping and overseeing transactional and correlated undertakings within companies (Kaplan & Haenlein, 2010). They have also facilitated the establishment and communication of brands (Cruz Rincon et al, 2022;Sahaym et al, 2021).…”
Section: Introductionmentioning
confidence: 99%